Mechanisms for the creation of intrinsic electron-hole trapping centers in a CaSO4 crystal - Nurakhmetov, T; Zhangylyssov, K. B.; Zhunusbekov, A. M.; Daurenbekov, D. H.; Alibay, T. T.; Sadykova, B.M.; Yussupbekova, B.N.; Tolekov, D.A. (Eurasian Journal of Physics and Functional Materials, 2026)
The mechanism of creation of electron-hole trapping centers in CaSO4 at 15-300 K was investigated by the methods of vacuum-ultraviolet and thermoactivation spectroscopy. It is shown that electron-hole trapping centers are formed upon trap of electrons in the anionic complexes SO2. and localization 4 of holes in the form of SO. radical. Based on the measurement of the spectrum of excitation of 4 long-wavelength recombination emission at 3.0-3.1 eV and 2.7 eV, the energy distance of the formed electron-hole trapping centers was estimated (4.43 eV and 3.87 eV).Recommended CitationNurakhmetov, T. N.; Zhangylyssov, K. B.; Zhunusbekov, A. M.; Daurenbekov, D. H.; Alibay, T. T.; Sadykova, B. M.; Yussupbekova, B. N.; and Tolekov, D. A. (2021) "Mechanisms for the creation of intrinsic electron-hole trapping centers in a CaSO4 crystal," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 3, Article 8.DOI: https://doi.org/10.32523/ejpfm.2021050308